Avian tropomyosin gene expression. - Lindquester, G J (1989)
Sequence analysis of overlapping fragments from a quail genomic library has revealed a tropomyosin gene consisting of 13 exons spaced over about 18 kilobase pairs of DNA. Skeletal muscle and smooth muscle transcripts share the same 5' untranslated sequence and may initiate from the same promoter. However, the regions encoding amino acids 39-80 and 258-284 are specific to each muscle type. The two sets of exons encoding these regions undergo mutually exclusive alternative splicing in a tissue-specific manner as determined by Northern blots and S1-nuclease protection. Similarly, the 3' ends of the transcripts are different in skeletal muscle and smooth muscle, and each contains two polyadenylation signals which appear to be utilized in vivo. The avian alpha-tropomyosin gene is not expressed in cardiac muscle. The sequence of the gene shows great homology with other muscle-specific tropomyosins and includes a region homologous to the amino terminus of nonmuscle tropomyosins.